Detection of sibutramine and phenolphthalein in functional foods using capillary electrophoresis. Issue 3 (22nd December 2015) - Wang, Dan; Man, Ranru; Shu, Ming; Liu, Huitao; Gao, Yuan; Luan, Feng
Abstract : Detection of sibutramine and phenolphthalein in functional foods by using capillary electrophoresis. Abstract : A simple method has been established for the simultaneous detection of sibutramine and phenolphthalein by using capillary electrophoresis. A mixture of 20 mM phosphate buffer and 20 mM sodium dodecyl sulfate was used as running buffer (pH 11.0). Analysis was carried out at a detection wavelength of 223 nm under a separation voltage of 25 kV at 20 °C. The limits of detection (LODs) were 0.03 μg mL −1 for sibutramine and 0.18 μg mL −1 for phenolphthalein. The linear ranges of the method were 0.1–50 μg mL −1 for sibutramine and 0.8–50 μg mL −1 for phenolphthalein. The proposed method has been successfully applied for the detection of the two target chemicals in functional foods, with satisfactory recovery ranging from 95.3% to 103.4%.